Ejecución de un examen especial a la cuenta inventarios de la empresa “Sait Samaniego Iturralde S.A” correspondientes al periodo enero 1 al31 diciembre del 2009 - Cajas Peñaherrera, Ana Mercedes (2013)
This work is the carrying out of a special exam to the inventory count of “Sait Samaniego Iturralde S.A” enterprise, related to January 01st to December, 2009 period. The auditory about financial states is very important to the spending control of an enterprise or institution. This work is based on doing an auditory within the financial states in the inventory counts of an enterprise of the trading sector.Besides, some auditory tests were done to the significative spending inventory according to the turn of the company business. In the first chapter we have developed the theoretical mark, in order to mention the definitions of: Administrative and Financial Management, Accounting, Internal Control, Auditory, Financial Auditory and Special Exam.The second chapter includes the auditory focus. To develop it we make a short description about the business knowledge. We determine preliminary and analytic process, so that the application of statistics techniques. That is why we made a diagnostic about the situation of the enterprise determining that there are not internal control regulations.In the third chapter, some auditory tests to the inventory spending were done. These tests let us to determine some significant rewards and verify the controls fulfillment. In every test we describe its objective, procedure, conclusions and recommendations according to the settlement reasoning. The application of the exam determined that the department of accounting is the responsible to the management and control of the inventories, which include too much process that starts with the plan until the sale and register of the merchandise. Then it makes difficult to control better and provokes deviations about the same things.In order to express an opinion to know if the financial states showed are reasonable and prepared according to the Principles of the Accounting Generally Accepted. For making that exam we collected and analyzed the information of documents which served to verify the procedures applied in the Accounting and in the Administrative, Financial processes giving progress and organizer improvement of the entity.